2004
DOI: 10.1002/pssa.200405167
|View full text |Cite
|
Sign up to set email alerts
|

Optically stimulated luminescence dosimetry on CVD diamond films

Abstract: Diamond thin films chemically vapor deposited containing different B/C concentration in the range of 2000 -20 000 ppm were exposed to a β-ray dose of 0.8 -3000 Gy. The optically stimulated luminescence (OSL) response of previously irradiated samples was excited with light of 470 nm at room temperature. The OSL decay curves were measured and found them to be a function of the dose exposure. The remaining thermoluminescence (TL) glow curve after optical stimulation indicates the existence of main charge carriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…AG is caused by slow radiative recombination (phosphorescence) of electrons thermally released from filled shallow traps into the conduction band 4, 5. Stimulation with infrared or visible light of CVD diamond that has previously been exposed to ionizing or UV radiation creates intense luminescence referred as OSL 6–10. OSL is caused by interaction of the stimulating light with electrons trapped in optically active traps.…”
Section: Introductionmentioning
confidence: 99%
“…AG is caused by slow radiative recombination (phosphorescence) of electrons thermally released from filled shallow traps into the conduction band 4, 5. Stimulation with infrared or visible light of CVD diamond that has previously been exposed to ionizing or UV radiation creates intense luminescence referred as OSL 6–10. OSL is caused by interaction of the stimulating light with electrons trapped in optically active traps.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent investigations have shown that CVD diamond may be used as optically stimulated luminescence (OSL) detectors and dosimeters [19,20]. Furthermore, recent investigations have shown that CVD diamond may be used as optically stimulated luminescence (OSL) detectors and dosimeters [19,20].…”
Section: B)mentioning
confidence: 99%
“…Diamond films made using the chemical vapor deposition process, with various impurities to enhance radiation response, have been studied and shown to be effective dosimeter materials for radiation doses from 0.8 Gy to 3 kGy using OSL analysis (Barboza-Flores et al, 2004). Natural diamond has its own impurities (responsible for color and other qualities), and the radiation sensitivity for a particular gemstone would be determined a posteriori as part of the dosimetric analysis, as noted above.…”
Section: Optical Stimulation Of Fortuitous Dosimetersmentioning
confidence: 99%